The Influence of Employee Work Performance on Loyalty and Leadership Style - Azim, Muhammad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This research aims to analyze the influence of employee work performance on loyalty and the role of leadership style in this relationship. Optimal work performance is expected to increase employee loyalty, while leadership style is expected to play an important role in strengthening or weakening this relationship. The research method used was a survey with data collection through questionnaires distributed to 150 employees from various companies. The collected data was analyzed using descriptive statistical techniques, Pearson correlation, and multiple linear regression. The research results show that there is a significant positive relationship between employee work performance and their level of loyalty, with a correlation value of 0.65 (p < 0.01). In addition, transformational leadership style was proven to have a significant positive influence on these two variables, namely work performance and employee loyalty (β = 0.70, p < 0.01 for performance; β = 0.60, p < 0.01 for loyalty). In contrast, transactional and autocratic leadership styles do not show a significant influence on performance and loyalty. These findings indicate that good work performance is closely related to employee loyalty, and the application of a transformational leadership style can strengthen this relationship. This research suggests companies apply an inspiring and empowering leadership style and provide appropriate rewards for good performance to increase employee loyalty. This study also notes several limitations, such as the limited sample size, and recommends further studies with larger sample sizes and more varied methods